Request to undertake part of Contractor's All Risk insurance premium - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the request to undertake part of Contractor's All Risk insurance premium of BRACU new campus project.